The Effect of Perceived Organizational Support (POS), Job Demand and Job Satisfaction on Employee Work Enggagement at PT Smart Glove Tanjung Morawa - Purba, Yulia; Jullimursyida, Jullimursyida; Khairawati, Khairawati; Iis, Em Yusuf; Faliza, Nur (AIBPM Publisher, 2023)
The international database that includes various industries shows that on average, only 20% of employees are engaged in their work, 20% are at a low point in their job, and the remaining 60% work without using their resources. This research aims to ascertain how employee work engagement at PT Smart Glove Tanjung Morawa is impacted by perceived organizational support (POS), job demand, and job satisfaction. This quantitative study uses a questionnaire as a data collection tool distributed to 100 employees in the PT Smart Glove Tanjung Morawa production department using a Likert scale. The results indicate that perceived organizational support (POS) has a positive and significant influence on employee work engagement at PT Smart Glove Tanjung Morawa; job satisfaction also has a positive and significant effect on employee work engagement at PT Smart Glove Tanjung Morawa; and job demand has a negative but significant influence on employee work engagement at PT Smart Glove Tanjung Morawa.